Plastid Phylogenomic Data Offers Novel Insights Into the Taxonomic Status of the Trichosanthes kirilowii Complex (Cucurbitaceae) in South Korea - Park, Inkyu; Song, Jun-Ho; Yang, Sungyu; Chae, Sungwook; Moon, Byeong Cheol (Frontiers in Plant Science, 2021)
Trichosanthes is a genus in Cucurbitaceae comprising 90–100 species. Trichosanthes species are valuable as herbaceous medicinal ingredients. The fruits, seeds, and roots of species such as T. kirilowii and T. rosthornii are used in Korean traditional herbal medicines. T. rosthornii is only found in China, whereas in South Korea two varieties, T. kirilowii var. kirilowii and T. kirilowii var. japonica, are distributed. T. kirilowii var. kirilowii and T. kirilowii var. japonica have different fruit and leaf shapes but are recognized as belonging to the same species. Furthermore, although its members have herbal medicine applications, genomic information of the genus is still limited. The broad goals of this study were (i) to evaluate the taxonomy of Trichosanthes using plastid phylogenomic data and (ii) provide molecular markers specific for T. kirilowii var. kirilowii and T. kirilowii var. japonica, as these have differences in their pharmacological effectiveness and thus should not be confused and adulterated. Comparison of five Trichosanthes plastid genomes revealed locally divergent regions, mainly within intergenic spacer regions (trnT-UGU–trnL-UAA: marker name Tri, rrn4.5–rrn5: TRr, trnE-UUC–trnT-GGU: TRtt). Using these three markers as DNA-barcodes for important herbal medicine species in Trichosanthes, the identity of Trichosanthes material in commercial medicinal products in South Korea could be successfully determined. Phylogenetic analysis of the five Trichosanthes species revealed that the species are clustered within tribe Sicyoeae. T. kirilowii var. kirilowii and T. rosthornii formed a clade with T. kirilowii var. japonica as their sister group. As T. kirilowii in its current circumscription is paraphyletic and as the two varieties can be readily distinguished morphologically (e.g., in leaf shape), T. kirilowii var. japonica should be treated (again) as an independent species, T. japonica.